Relative intimacy : fathers, adolescent daughters, and postwar American culture - Devlin, Rachel (Gender & American culture., 2005)
Rachel Devlin argues that postwar culture fostered a father-daughter relationship characterized by new forms of psychological intimacy. The pervasiveness of depictions of father-adolescent daughter eroticism on all levels of culture raises questions about the extent of girls' independence and the character of fatherhood during the 40s and 50s.